Case report: Local cryoablation combined with pembrolizumab to eliminate lung metastases from ovarian clear cell carcinoma - Meng, Liangliang; Zhang, Zhongliang; Zhang, Xiao; Zhang, Xiaobo; Wei, Yingtian; Wu, Bin; Xue, Xiaodong; Zhang, Xin; He, Xiaofeng; Xiao, Yueyong (Frontiers in Immunology, 2022)
Ovarian clear cell carcinoma has a high recurrence rate with poor prognosis and is generally not sensitive to conventional platinum-based chemotherapy. Its less frequent occurrence of mutations such as BRCA limited the targeted therapies. Immunotherapy is not currently recommended as a first-line agent for ovarian cancer, and most patients are not yet able to benefit from it. Cryoablation can be used to treat solid systemic tumors, including ovarian cancer metastases, and can produce a limited anti-tumor immune response. The anti-tumor effects of cryoablation combined with immunotherapy have not been adequately confirmed. This study reports a case of a patient with ovarian clear cell carcinoma who underwent conventional adjuvant chemotherapy after initially surgical resection of the tumor. Unfortunately, cancer recurred and metastasized to the abdominal wall. After a series of painful chemotherapy and a second surgery, the cancer was still not effectively controlled, and the patient developed extensive metastases in the lung. The patient's PD-L1 expression level also did not support solo immunotherapy. We pioneered the use of cryoablation to first eradicate the most significant lesion in the upper lobe of the left lung and then combined it with the PD-L1 inhibitor pembrolizumab to treat the patient with immunotherapy, which resulted in the complete eradication of the other multiple metastases in the lung and saved the patient's life. Although the precise mechanism of action has not yet been explored, we have reason to believe that the combination of cryoablation and immune checkpoint inhibitor has a powerful synergistic anti-tumor effect, which is yet to be confirmed by more basic research and clinical applications in the next step.